2016
DOI: 10.1186/s12906-016-1262-2
|View full text |Cite
|
Sign up to set email alerts
|

Traditional medicine practices among community members with diabetes mellitus in Northern Tanzania: an ethnomedical survey

Abstract: BackgroundDiabetes is a growing burden in sub-Saharan Africa where traditional medicines (TMs) remain a primary form of healthcare in many settings. In Tanzania, TMs are frequently used to treat non-communicable diseases, yet little is known about TM practices for non-communicable diseases like diabetes.MethodsBetween December 2013 and June 2014, we assessed TM practices, including types, frequencies, reasons, and modes, among randomly selected community members. To further characterize TMs relevant for the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 25 publications
5
33
0
Order By: Relevance
“…This is a phenomenon observed in other communities of Brazil [5] and of the world [47, 48] and there is a need to give attention to the possible consequences of drug interaction.…”
Section: Discussionmentioning
confidence: 99%
“…This is a phenomenon observed in other communities of Brazil [5] and of the world [47, 48] and there is a need to give attention to the possible consequences of drug interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Only one of the seven studies was drawn from a large sample of patients with hypertension (n=500) and the reported prevalence in this case was 24%. 106 TCAM product use by patients with diabetes varied across the four identified studies drawn from smaller samples, with a higher rate reported in Tanzania (77.1%) 107 compared with Nigeria (46%), 43 Guinea (33%) 108 and Kenya (12.4%). 109 With regard to cancer, the available literature reports a high use of TCAM among patients with cancer in Sub-Saharan Africa (Nigeria: 65% 34 ; Ethiopia: 79% 110 ; Ghana: 73.5% 56 ), although one Nigerian study did report a lower rate of use specifically for TCAM services.…”
Section: Prevalence Of Tcam Use In Health Subpopulations Pregnancy Cmentioning
confidence: 99%
“…For several decades, lemongrass has been reported to be extensively used for a number of folkloric, cosmetic, and nutritional purposes. In Nigeria, Egypt, South Africa and Tanzania, lemongrass tea (LGT) is consumed for the treatment of DM and other related disorders such as hypertension and obesity [9][10][11][12]. Major active ingredients of LGT were phenolics, flavonoids and terpenoids of which the contents were reported to be higher compared to cold water extract [13].…”
Section: Introductionmentioning
confidence: 99%